COMPLEXITIES BEHIND THE JAVANESE SHROUNDS: UNRAVELING TEXTILE SYMBOLISM FOR THE DEAD THROUGH MIKHAIL BAKHTIN’S HETEROGLOSSIA - Faizin, Asha Kun Nayla; Kartika, Ganang Dwi (International Review of Humanities Studies, 2025)
The shroud, a textile used to wrap and accompany humans in death, is far from a simple object. Within Islamic traditions, the white cloth applied to the deceased's body takes on various changes, modifications, and deeper meanings when individuals contextualize their own beliefs and experiences through it. This study focuses on the shroud's role in Islamic death rituals in Java, revealing a multiplicity of meanings as theorized by Mikhail Bakhtin's concept of heteroglossia. By employing a pragmatic semiotic approach, this research interprets and analyses the symbols that emerge from the contextualization of these textiles within Javanese death rituals. The study’s significance lies in its exploration of the cultural richness and symbolism associated with shrouds in Javanese Islam, thereby shedding light on the intricate interplay between religion and culture in shaping human experiences and beliefs around death.